Analisis Normalisasi Sungai Baubau - Alianti, Alianti; Sukri, Ahmad Syarif; Sudardjat, Catrin; Ilham, Vickky Anggara (Sultra Civil Engineering Journal (SCiEJ), 2021)
The durability of the road flexural pavement structure is largely determined by the performance of each layer. One of these factors is the strength and resilience of the subbase. Compaction in accordance with applicable standards will produce roads with good quality so that the road life is longer and there is less damage. The purpose of this study is to analyze the carrying capacity using CBR, the value of the field density with the sand cone test and the correlation of the CBR value and the Sand cone value of the B grade foundation layer on the Tugu Munajah network. The research method used is laboratory and field testing combined with a descriptive statistic approach. The results of the study indicate that the carrying capacity using the CBR amounted to 55.02% <60%, the density value field with sand cone test of 72.50% <90%. Correlation of CBR and Sand cone value at the base layer (sub base course) is very strong at 0.998.